Analisis Faktor-Faktor Psikologis Yang Mempengaruhi Keputusan Konsumen: Pendekatan Data Mining Menggunakan Rapidminer - Uhti Lestar; Anna Dina Kalifia (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Literary psychology is a branch of psychology that studies the interaction between psychology and literature. It involves analyzing and understanding how psychological elements, such as emotion, motivation, perception, and personality, can be understood through literary works. Literary psychology tries to explain and understand human experiences expressed in literary works, as well as how literary works can influence and affect readers emotionally and psychologically.